GUIDED BONE REGENERATION TECHNIQUES IN ALVEOLAR BONE RECONSTRUCTION - Doriana Agop-Forna; Roland Törok; Bianca Törok; Cosmin Cretu; Cristian Budacu; Norina Forna (Romanian Society of Oral Rehabilitation, 2022)
Various alveolar bone augmentation techniques are used in the reconstruction of post-extraction alveolar sites and in the reconstruction of post-cystectomy bone defects. Guided tissue regeneration techniques use grafting materials with osteogenic, osteoinductive, or osteoconductive properties as well as membranes as a barrier to epithelial proliferation and as a stimulating environment for osteogenesis. The sinus lifting technique associated with bone addition is used in the case of implant sites with reduced height and thickness in the posterior areas of the maxillary arch as follows: post-extraction, severe periodontal damage, severe bone resorption, reduced distance between the highest point of the alveolar ridge and the sinus floor, the extension of the sinus in the area initially occupied by the dental roots. S-GBR technique allows to maintain the regenerative bone space due to osteosynthesis screws that support the space of the bone regeneration compartment, while pericardial membrane to protect the area from regeneration from soft tissue invasion). GBR techniques can be performed, in relation to local conditions and pathology, through standard bone addition protocols, in combination with sinus lifting techniques or through specific techniques (S-GBR). The implant-prosthetic treatment plan must pay particular attention to the alveolar bone reconstruction stage through guided bone regeneration techniques that will ensure the optimal positioning of dental implants in the context of restoring biomechanical and functional conditions through fixed or removable prosthetic restorations with implant support.